2017
DOI: 10.4301/s1807-17752017000200006
|View full text |Cite
|
Sign up to set email alerts
|

App Adoption and Switching Behavior: Applying the Extended Tam in Smartphone App Usage

Abstract: The increasing use of mobile applications have been escalating with the increasing use of smartphones. In the present study, we examine (a) the adoption behavior of mobile apps using the extended TAM framework, and (b) whether adoption leads to subsequent use behavior and switching intentions. Based on data collected from two surveys in India we test the conceptual model of extended TAM and the effects of behavior on switching intentions using factor analysis and structural equation modeling. The major finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 51 publications
5
44
1
3
Order By: Relevance
“…Adapting TRA, Davis [63] developed the technology acceptance model (TAM), in which perceived usefulness and perceived ease of use were postulated as key constructs influencing the intention of a person for technology acceptance. TAM remains a dominant framework in the literature and has been extensively used to study adoption behavior in areas like mobile apps [66], tourism [67], and mobile financial services [68]. However, the model has received criticism because of its inability to capture negative emotions and intrinsic motivations [69].…”
Section: Unified Theory Of Acceptance and Use Of Technology 2 (Utaut2)mentioning
confidence: 99%
“…Adapting TRA, Davis [63] developed the technology acceptance model (TAM), in which perceived usefulness and perceived ease of use were postulated as key constructs influencing the intention of a person for technology acceptance. TAM remains a dominant framework in the literature and has been extensively used to study adoption behavior in areas like mobile apps [66], tourism [67], and mobile financial services [68]. However, the model has received criticism because of its inability to capture negative emotions and intrinsic motivations [69].…”
Section: Unified Theory Of Acceptance and Use Of Technology 2 (Utaut2)mentioning
confidence: 99%
“…The growth and adoption rates of mobile apps are amazingly high. The rapid adoption of apps is attributed to their ease of use and the quick access to desired content [13]. However, not all mobile apps see activity.…”
Section: The Popularity Of Mobile Appsmentioning
confidence: 99%
“…UTAUT integrates key factors including expected performance of the new technology, effort, and social influences, with moderating variables such as age, gender, experience, and voluntariness. These conceptual MIS models are then explored empirically as the impact of specific variables that influence technology adoption behavior is identified (Venkatesh et al, 2012;Kamal, 2006;Ghezzi et al, 2013;Roy, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on technology adoption in management information systems (MIS) identified several conceptual models and general frameworks for such decisions including the technology acceptance model (TAM) and the unified theory of acceptance and use of technology (Venkatesh et al, 2003(Venkatesh et al, , 2012Gangwar et al, 2014;Roy, 2017) as well as specific variables and success factors that influence adoption behavior (e.g. Kamal, 2006;Ghezzi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%